2023
DOI: 10.1071/wf22198
|View full text |Cite
|
Sign up to set email alerts
|

An improved spatio-temporal clustering method for extracting fire footprints based on MCD64A1 in the Daxing’anling Area of north-eastern China

Abstract: Background. Understanding the spatio-temporal dynamics associated with a wildfire event is essential for projecting a clear profile of its potential ecological influences. Aims. To develop a reliable framework to extract fire footprints from MODIS-based burn products to facilitate the understanding of fire event evolution. Methods. This study integrated the Jenks natural breaks classification method and the density-based spatial clustering of applications with noise (DBSCAN) algorithm to extract the fire footp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…This algorithm is an extension of the well-known DBSCAN algorithm [50]. DBSCAN has been widely used to identify dense fire clusters [51][52][53][54][55]. Unlike DBSCAN, which relies on a single global density parameter ε (epsilon), HDBSCAN operates by performing clustering over varying ε values and integrating the results to identify the clustering that demonstrates the best stability across these values [56].…”
Section: Correlation Analysis and Cluster Analysismentioning
confidence: 99%
“…This algorithm is an extension of the well-known DBSCAN algorithm [50]. DBSCAN has been widely used to identify dense fire clusters [51][52][53][54][55]. Unlike DBSCAN, which relies on a single global density parameter ε (epsilon), HDBSCAN operates by performing clustering over varying ε values and integrating the results to identify the clustering that demonstrates the best stability across these values [56].…”
Section: Correlation Analysis and Cluster Analysismentioning
confidence: 99%
“…It is reported that data can be properly classified using this method, with minimal information loss [64]. The method and its variants have been successfully applied in the field of remote sensing and GIS in classification and object extraction tasks based on quantitative data [65][66][67]. After REA processing, DEM data in gully areas exhibited aggregation patterns in the gully floor and inter-gully regions.…”
Section: Extracting Mask Of Erosion Gullies Using Reamentioning
confidence: 99%